Effects of Intercropping and Mowing Frequency on Biological Nitrogen Fixation Capacity, Nutritive Value, and Yield in Alfalfa (Medicago sativa L. cv. Vernal) - Yao Wang; Jinsong Zhang; Chunxia He; Ping Meng; Jie Wang; Jun Gao; Pan Xue (Plants)
Intercropping with legume forages is recognized as an effective strategy for enhancing nitrogen levels in agroforestry, while mowing may influence nitrogen fixation capacity and yield. This study investigated the rooting, nitrogen fixation, nutritive value, and yield of alfalfa (Medicago sativa L.) under intercropping and varying mowing frequencies (CK, 2, and 3) from 2021 to 2023, using walnut (Juglans regia L.) and alfalfa as experimental subjects. The results indicated that intercropping suppressed root growth, whereas increased mowing frequency stimulated root development in the topsoil (0–20 cm). Specifically, the average root length density, root surface area, and root volume from the twice- and thrice-mowed treatments increased by 18.26, 17.45, and 4.15%, respectively, in comparison to the control. The δ15N values of the intercropped alfalfa were significantly lower than those of the monocropped alfalfa (p < 0.05), with the δ15N values of the mowing-thrice treatment increasing by an average of 38.61% compared to the control. Intercropping suppressed alfalfa yield but did not affect the total nitrogen content in the leaves or the nutritive value, and all mowing treatments resulted in land equivalent ratios (LERs) greater than 1. Furthermore, increased mowing frequency enhanced both the nutritive value and yield of alfalfa. Our study suggests that intercropping with walnut can improve biological nitrogen fixation in alfalfa, and that adopting a mowing-thrice regime can optimize yield and nutritive value.